Influence of the synthesis route on the formation of 12R/10H-polytypes and their magnetic properties within the Ba(Ce, Mn)O3 family. (18th August 2014) - Macías, Mario A.; Mentré, Olivier; Pirovano, Caroline; Roussel, Pascal; Colis, Silviu; Gauthier, Gilles H.
Abstract : A selective synthesis of 12 R /10 H polytypes within the Ba–Ce–Mn–O family can be induced by a Mn precursor. Abstract : The influence of the Mn precursor on the formation of polytypes was studied within the Ba–Ce–Mn–O system. Minor changes in the mean oxidation state of Mn cations guide the reaction route through different pathways to obtain the iso-stoichiometric 12 R -Ba4 CeMn4 O12− δ or 10 H -Ba5 Ce1.25 Mn3.75 O15− δ compounds. This behaviour was controlled using MnO2 or MnCO3 as starting chemical precursors. The understanding of such tendencies allowed the synthesis of the new 10 H -Ba5 Ce0.83 Mn4.17 O15− δ composition through a two-step reaction route. This compound crystallizes in a hexagonal symmetry with space group P 63 / mmc (No. 194) and cell parameters a = b = 5.77650(6) Å and c = 23.8590(4) Å. Its main characteristic is the presence of pure [Mn4 O15 ] oligomers, establishing a difference with respect to the already known 10 H -Ba5 Ce1.25 Mn3.75 O15 polytype for which the principal feature was a mixed metal occupancy within [Ce0.25 Mn3.75 O15 ] tetramers. This difference generates strong antiferromagnetic (AFM) exchanges, contrary to the metamagnetic-like transition observed in 10 H -Ba5 Ce1.25 Mn3.75 O15 . It is concluded that full Mn occupancy in [Mn3 O12 ] or [Mn4 O15 ] sub-units induces a robust AFM character.